A specific energy-based ball mill model: From batch grinding to continuous operation. (February 2016) - Shi, Fengnian; Xie, Weiguo
Highlights: A specific energy-based ball mill model for continuous operation. The Whiten classification efficiency equation used for the ball mill discharge function. Ore-specific and size-dependent breakage function incorporated in the model. The model was tested with a number of full scale ball mill operation survey data. Abstract: A specific energy-based size reduction model for batch grinding ball mills was reported in a previous paper (Shi and Xie, 2015). A discharge function modified from the Whiten classification efficiency equation has been incorporated in the size reduction model to extend its applications from batch grinding to continuous operation. Five sets of the industrial ball milling survey data were used to validate the ball mill model. The data were acquired from four full scale ball mills covering primary and secondary grinding duties in a gold concentrator and a PGM concentrator. In all cases, the model fits the ball mill operational data well. Features of the specific energy-based ball mill model include the use of an ore-specific and size-dependent breakage function, whose parameters are independently measured with a fine particle breakage characterisation device, the JKFBC. This allows simulations of the effect on ground product size distribution of changing ore breakage characteristics. The model utilises separate selection function and discharge function, which permits the investigation of the influences of mill operational conditions on grinding performance.